The interconnection of parent-child relationships with the propensity to manipulating at senior schoolboys - VIKHREVA, Ludmila (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
This article considers the problem of the relationship between the characteristics of parent-child relationships and manipulative installations that manifest in the behavior of adolescents, also described the practical results obtained in the research.